Expeditious Synthesis, Antimicrobial and Antimalarial Activities of Novel Heterocycles Bearing Imidazole-oxadiazole Based Hybrid Pharmacophores - Balaji, K.; Bhatt, P.; Jha, A. (Drug Research, 2016)
A facile synthesis of 2-substituted-5-amino-oxadiazole derivatives has been achieved by refluxing/sonicating a mixture of semicarbazide with various aromatic acids in conc. sulphuric acid alone. The isolated products were further condensed with p-dimethylaminobenzaldehyde/p-hydroxybenzaldehyde to obtain respective imino derivatives. Finally, some potentially biologically active imidazole analogues were obtained by reacting ammonium acetate and 5-bromoisatin with the synthesized imino products. All the newly synthesized compounds were thoroughly characterized by standard analytical techniques. These imidazole-oxadiazole hybrid compounds were also evaluated for their antimicrobial and antimalarial activities. The compounds all exhibited moderate to significant antimicrobial activity (6–10 mm, zone of inhibition) and promising antimalarial activity (IC50 0.037–0.100 µM). This report entails a detailed synthetic procedure, spectroscopic elucidation and activities of the synthesized compounds.
Keywords: oxadiazole derivatives; antimicrobial; antimalarial; ultrasonication